EFEKTIVITAS PENERAPAN PROJECT-BASED LEARNING BERBASIS OUTDOOR STUDY DENGAN BANTUAN MICROSOFT TEAMS UNTUK MENINGKATKAN PEMAHAMAN KONSEP - Dyah Binti Astuti; Mohammad Budiyanto (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This research aimed to describe the effectiveness of implementing project-based learning with outdoor study using the assistance of Microsoft Teams to increase conceptual understanding from the material about heat and its transfer. Participants in this research were 31 students of class VII in SMPN 42 Surabaya. This research used a pre-experimental with one group pretest-posttest design. Data collection techniques were conducted by pretest-posttest and questionnaire responses. The result from a paired t-test showed a significant difference between pretest and posttest scores to increase students' conceptual understanding. The N-Gain test pointed out that 55% of students were in the medium category while the other 45% were in the high category after implementing project-based learning on an outdoor study using Microsoft Teams. Students' responses to the learning process indicated that 81.41% had positive responses. Based on the result, it can be concluded that applied learning effectively could increase students' conceptual understanding